2017
DOI: 10.1002/cpim.26
|View full text |Cite
|
Sign up to set email alerts
|

Basic Multicolor Flow Cytometry

Abstract: Multicolor flow cytometry is a rapidly evolving technology that uses multiple fluorescent markers to identify and characterize cellular subpopulations of interest, allowing rapid analysis on tens of thousands of cells per second, with the possibility of isolating pure, viable populations by cell sorting for further experimentation. This unit covers the tools needed by the beginning immunologist to plan and run multicolor experiments, with information on fluorochromes and their characteristics, spectral spillov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 46 publications
(50 reference statements)
0
68
0
2
Order By: Relevance
“…Data from studies involving multi-centers, each performing its own supervised analysis, have indicated that manual gating introduces the largest variable in standardized experiments (17)(18)(19)(20)(21)40). Data from studies involving multi-centers, each performing its own supervised analysis, have indicated that manual gating introduces the largest variable in standardized experiments (17)(18)(19)(20)(21)40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from studies involving multi-centers, each performing its own supervised analysis, have indicated that manual gating introduces the largest variable in standardized experiments (17)(18)(19)(20)(21)40). Data from studies involving multi-centers, each performing its own supervised analysis, have indicated that manual gating introduces the largest variable in standardized experiments (17)(18)(19)(20)(21)40).…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers will begin with the manufacturer recommended titration and test multiple doses until an optimal stain index is achieved (20)(21)(22)(23)(24). Initial titration of antibodies is a wellestablished criterion for good experimental design.…”
Section: Antibody Validationmentioning
confidence: 99%
“…As a result, critical methods of instrument standardization and calibration (27)(28)(29)(30)(31), panel and experimental design (32)(33)(34)(35)(36), sample preparation and controls (37)(38)(39), spillover correction (40), and data presentation and publication (41,42) are emphasized in various seminal publications. As a result, critical methods of instrument standardization and calibration (27)(28)(29)(30)(31), panel and experimental design (32)(33)(34)(35)(36), sample preparation and controls (37)(38)(39), spillover correction (40), and data presentation and publication (41,42) are emphasized in various seminal publications.…”
Section: Existing Flow Cytometry Resources and Guidelines On Preparinmentioning
confidence: 99%
“…Gating on live T cells (stained with a viability dye and anti-CD4 or anti-CD8), we reproducibly find that 60-95% are GFP+. For details on performing flow cytometry analysis, see Maciorowski, Chattopadhyay, & Jain (2017).…”
Section: Day 2: Repeat Transduction (Optional)mentioning
confidence: 99%